In the absence of clocks - Shores-Arguello, Jacob (Crab Orchard award series in poetry., 2013)
The poet takes readers on a voyage through Ukrainian life. Set during the turmoil of the 2004 Orange Revolution, when the country trembled in the wake of political corruption and public outrage, these lyrics of a revolution provide a glimpse into a world at once foreign and familiar. Throughout the collection are the iconic images and myriad juxtapositions of Ukrainian life: wolves howling in the snow and bakers pounding early-morning loaves of bread; farmlands and cities alike rocked by political transformation; gypsies and protesters; opulent images of Byzantium and the concrete ghosts of Chernobyl - all meet here at the crossroads of East and West, democracy and communism, reality and mythology.